Relationship Between Frequency Of Breastfeeding With Breastmilk Production Mother post Partum In Region Work Puskesmas Peusangan Selatan Bireuen City Year 2017 - angriani, riana -; Sudaryati, Etti; Lubis, Zulhaida (Jurnal Muara Sains, Teknologi, Kedokteran dan Ilmu Kesehatan, 2018)
Lower breastfeeding is a service for infant growth, if exclusive breastfeeding will not, infants will be more susceptible and greater for growth and stamina of children where the prevalence of post partum mothers who produce milk is not fluent that is equal to 60% . This study aims to determine the relationship of data with the smooth production of mother's milk post partum in the Working Area of Peusangan Selatan Public Health Center of Bireuen Regency of Aceh Province. This type of research is an observational analytic study using cross sectional design. The population of this study is all post partum mothers, in Peusangan Selatan Public Health Center report conducted in February-October 2017. The sample in this research is open 69 people. The data were analyzed by univariate to see the variables and bivariate with chi-square test to see the relation between the variables. Based on the result of the research to measure the relationship with the mother's milk production with p value = 0,019 PR = 2,438 (95% CI 1,261-4,711) . It was concluded that mothers with good facilities had an opportunity of 2,438 times to have breast milk production working with mothers with poor breastfeeding frequency.